1982
DOI: 10.1099/00221287-128-10-2469
|View full text |Cite
|
Sign up to set email alerts
|

Pectinases in Leaf Degradation by Aquatic Hyphomycetes: the Enzymes and Leaf Maceration

Abstract: All seven species of aquatic hyphomycetes tested produced both polygalacturonases and pectin lyases. The polygalacturonases were constitutive, whereas the pectin lyases were induced on pectic substrates at pH 6.5 and above. Some species could grow on pectic substrates at both pH 5 and pH 7; other species at pH7 only. Tricladium splendens grew as well on a polypectate substrate as it did on glucose. This fungus elaborated three endo-polygalacturonase isoenzymes, as did Articulospora tetracladia. Tetrachaetum el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 17 publications
4
40
0
Order By: Relevance
“…These results support the findings of Chamier & Dixon (1982b), who found that of seven species of aquatic Hyphomycetes investigated, only two grew well on polypectate agar at pH 5, whereas all species did so at pH 7. The fungi used in our investigation were somewhat more acid-tolerant, possibly because of a selection in an acidic environment.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results support the findings of Chamier & Dixon (1982b), who found that of seven species of aquatic Hyphomycetes investigated, only two grew well on polypectate agar at pH 5, whereas all species did so at pH 7. The fungi used in our investigation were somewhat more acid-tolerant, possibly because of a selection in an acidic environment.…”
Section: Discussionsupporting
confidence: 82%
“…These authors suggested that this was due to inhibition of the breakdown of cell wall components. Chamier & Dixon (1982b) showed that pectin degradation and leaf maceration by selected aquatic Hyphomycetes was inhibited at pH < 5 . Pectate lyase, an important enzyme in tissue maceration (Friend, 1977, and references therein) was not found in cultures grown at pH <6-5.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with other observations that all showed a preference of Gammarus to fungi-conditioned leaves (Ba¨rlocher & Kendrick, 1975;Sutcliffe et al, 1981;Grac¸a et al, 1993a). This preference is explained from the presence of aquatic hyphomycetes that degrade the pectic polymers in leaf cell walls (Chamier & Dixon, 1982). These hyphomycetes breakdown leaf tissue, making it easier for Gammarus to consume and allowing for a faster overall consumption rate (Sutcliffe et al, 1981).…”
Section: Discussionsupporting
confidence: 91%
“…Microbes, aquatic hyphomycetes in particular, macerate the leaf matrix by the activities of extracellular enzymes (Chamier and Dixon 1982), convert organic carbon into fungal biomass (mycelium and conidia; Gessner and Chauvet 1994;Gulis and Suberkropp 2003;Ferreira et al 2012), and mineralize it (Gulis and Suberkropp 2003), which leads to litter mass loss (Hieber and Gessner 2002). The accumulation of fungal biomass and the maceration of litter increase the litter quality for invertebrate detritivores, whose feeding activities lead to further litter mass loss (Bärlocher and Kendrick 1975;Graça et al 2001;Chung and Suberkropp 2009).…”
Section: Introductionmentioning
confidence: 99%